Energy and exergy analysis of a perlite expansion furnace - Gürtürk, Mert; Öztop, Hakan Fehmi; Hepbaslı, Arif (Springer International Publishing, 2014)
Utilization opportunities of perlite have made the product adaptable to numerous applications in the construction, industrial, chemical, horticultural and petrochemical industries. Applications of the perlite include filler, high and low temperature insulation, concrete aggregate, textured coatings, absorbent and carrier etc. Thus, perlite seems to be a very important material. In this paper, thermodynamics analysis of a perlite expansion furnace was performed. Both energy and exergy relations were derived for the considered system. Some parameters, such as losses, irreversibility and design etc., were used for determining the energy and exergy efficiencies. Based on the results of the analysis of the system, the energy and exergy efficiencies are calculated to be 66 and 26 %, respectively. Some recommendations were also made towards increasing the efficiency in the Turkish perlite industry. © Springer International Publishing Switzerland 2014.
Keywords: Energy; Exergy; Perlite; Perlite expansion furnace